Impact of an excise tax on the consumption of sugar-sweetened beverages in young people living in poorer neighbourhoods of Catalonia, Spain: a difference in differences study - Miguel Ángel Royo-Bordonada; Carlos Fernández-Escobar; Lorena Simón; Belen Sanz-Barbero; Javier Padilla (BMC, 2019)
Abstract Background Sugar-sweetened beverage consumption is contributing to the obesity epidemic. On 28 March 2017, Catalonia enacted a law levying an excise tax on sugar-sweetened beverages for public health reasons. The purpose of this study is to assess the impact of the tax on the consumption of sugar-sweetened beverages in Catalonia (Spain). Methods Before-and-after study to assess changes in the prevalence of consumption of sugar-sweetened beverages among 1929 persons aged 12 to 40 years residing in low-income neighbourhoods of Barcelona (intervention) and Madrid (control). Beverage consumption frequency was ascertained via a validated questionnaire administered during the month prior to the tax's introduction (May 2017) and again at 1 year after it had come into force. The effect of the tax was obtained using Poisson regression models with robust variance weighted using propensity scores. Results While the prevalence of regular consumers of taxed beverages fell by 39% in Barcelona as compared to Madrid, the prevalence of consumers of untaxed beverages remained stable. The main reason cited by more than two-thirds of those surveyed for reducing their consumption of sugar-sweetened beverages was the increase in price, followed by a heightened awareness of their health effects. Conclusions The introduction of the Catalonian excise tax on sugar-sweetened beverages was followed by a reduction in the prevalence of regular consumers of taxed beverages.